Breath Hydrogen Test in Lactose Malabsorption - Badriul Hegar; Hans A. Buller (Paediatrica Indonesiana, 1995)
Lactose is the most important source in mammalian milk. In normal children, Lactose is hydrolyzed by lactase, and directly absorbed into bloodstream by an active transport mechanism. The term of lactose malabsorption is reserved to patients in whom impaired intestinal lactose hydrolysis and uptake has been proven by an appropriate test. The severity of lactose malabsorption and the extent of symptoms vary widely and are the results of several factors such as the amount of ingested lactose, gastric emptying time, intestinal transit time, and colonic flora. The diagnosis of lactose malabsorption is based on clinical findings and the results of appropriate tests. The breath hydrogen test has obvious advantages for pediatric population because it is painless, non-invasive, sensitive and specific. In the absence of bacterial colonization in the small intestine, the elevation of the concentration of hydrogen in the expired air implies the arrival of lactose in the colon. The increasing respiratory excretion of hydrogen is indicative of a deficit of lactase in enterocyte brush border. This test can also be used to show the existence of bacterial growth. Dietary fiber, some drugs, preparation for colonoscopy, colonic pH, and diarrhea can influence the result of breath hydrogen test.